Effect of Volatility in the Naira - Dollar Exchange Rate on the volume of Imports to, and Exports from Nigeria - Dogo, Mela Yila; Aras, Osman Nuri (International Journal of Economics and Financial Issues, 2021)
We analyzed the effect of volatility in the Naira-Dollar exchange rate on the volume of imports to and exports from Nigeria between 1990 and 2019. Data for all variables, except volatility, were sourced from the Central Bank of Nigeria (CBN), the National Bureau of Statistics (NBS), and the International Financial Statistics. The volatility of the naira exchange rate was calculated from the model. The study employed both the autoregressive distributed lagged (ARDL) and exponential generalized autoregressive conditional heteroscedasticity (EGARCH) models to test for the short and long-run relationships between changes in the Naira-Dollar exchange rate and the volume of imports and exports. Volatility in the Naira-Dollar exchange rate was found to be related to the volume of imports to and exports from Nigeria in the long run with no short-run effects because of the pass-through effect to domestic inflation. The study recommends that government should sustain efforts at promoting exports and reducing imports to improve the trade balance. The study brings into perspective another way of looking at the long-run relationship between the Naira-Dollar exchange rate and Nigeria's trade balance. Keywords: Foreign exchange rate, foreign exchange market, Imports, Exports, The balance of trade, Nigeria. JEL Classifications: F14, F31, 024. DOI: https://doi.org/10.32479/ijefi.11799